In the midst of life we are in death - Ang, Jocelyn Peixun (2015)
In the Midst of Life We Are in Death is a visual interpretation of the artist’s exploration of the ideas of death and loss. This project is a journey she embarked on with the intention of expressing her fears and reservations towards death, while reminding herself about the people and things that she cares about in her life. Looking upon life itself as a reminder of death, she seeks to reconcile the two: to talk about death with life and vice versa. This series represents her candid emotions towards the impending losses in and of our lives.